Surgical Options for Pediatric Bilateral Vocal Cord Palsy: State of the Art - Trozzi, Marilena; Meucci, Duino; Salvati, Antonio; Tropiano, Maria Luisa; Bottero, Sergio (Frontiers in Pediatrics, 2020)
Management of pediatric bilateral vocal cord palsy (BVCP) is a controversial and challenging topic. It may represent a severe obstructive condition usually associated with respiratory distress and, in such condition, tracheostomy has been considered the gold standard for long time. Many surgical options have been described and used to increase the glottic space in BVCP11, with ongoing research of less invasive techniques. The challenge and the current trend in our department and in many major pediatric centers is to avoid tracheotomy through an early treatment. Many techniques introduced in the last decade reduced the number of tracheotomies and increased decannulation rate. Furthermore, we observed a recent increasing in attention to preserve the quality of the voice with new techniques, such as endoscopic arytenoid abduction lateropexy that is in our opinion an important innovation to improve glottic space with satisfactory voice result. We present a review of the literature about the evolution of the treatment options for pediatric BVCP during the years.